Impaired intratumoral natural killer cell function in head and neck carcinoma - Mele, Dalila; Pessino, Greta; Trisolini, Giuseppe; Luchena, Alberto; Benazzo, Marco; Morbini, Patrizia; Mantovani, Stefania; Oliviero, Barbara; Mondelli, Mario U.; Varchetta, Stefania (Frontiers in Immunology, 2022)
Natural killer (NK) cells are emerging as unique players in the immune response against cancer; however, only limited data are available on tumor infiltrating NK cells in head and neck squamous cell carcinoma (HNSCC), one of the most common cancer. Occurrence of HNSCC is closely related to the immune microenvironment, and immunotherapy is increasingly being applied to this setting. However, the limited success of this type of treatment in this tumor calls for further investigation in the field. Surgical HNSSC specimens of 32 consecutive patients were mechanically and enzymatically dissociated. Tumor cells were separated from infiltrating cells by short centrifugation and infiltrating NK cells were phenotypically and functionally characterized by multiple antibody staining and flow cytometry. Tumor infiltrating NK cells in HNSCC showed a peculiar phenotype predominantly characterized by increased NKG2A and reduced Siglec-7, NKG2D, NKp30 and CD16 expression. This phenotype was associated with a decreased ability to perform antibody-dependent cellular cytotoxicity (ADCC). However, NK, CD4 and CD8 shared an increment of glucocorticoid-induced tumor necrosis factor-related (GITR) costimulatory receptor which could be exploited for immunotherapy with agonistic anti-GITR antibodies combined with checkpoint inhibitors.